Faithful representation of accounting information according requirements width financial statements depending on international standard (IFRS-15) revenue from contracts with customers: Applied research in a sample of the joint stock companies listed on the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This study seeks to identify the possibility of achieving the property of faithful representation of accounting information and measure it by using the standard approach based on mathematical and statistical equations by comparing two financial periods before and after the application of (IFRS-15) Revenue from contracts with customers, during the period. (2014-2018), for the financial statements of the mixed joint stock companies listed on the Iraq Stock Exchange, which is one of the main pillars of the economic structure of the country, as a joint investment between the state and the private sector, and has importance in many aspects, including support for projects of public companies, S Absorption and employment of labor, as well as raising the production capacity to economic prosperity, which helps in promoting accounting disclosure and confidence in these lists by its users. The research reached a set of conclusions, the most important of which is that the application of the International Financial Reporting Standard (15) Revenue from contracts with customers in companies listed in the Iraqi market for securities achieve the property of the faithful representation of accounting information and thus gives confidence in the financial statements of its users. The research recommended the need to use mathematical and statistical methods in measuring the qualitative characteristics of accounting information in general, and the property of faithful representation in particular, according to the model adopted in this research, which enhances the reliability of financial statements.